2020
DOI: 10.1016/j.artd.2019.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Early failure of sequentially annealed polyethylene in total knee arthroplasty

Abstract: Improvements in the processing of polyethylene have led to a dramatic reduction in wear rates in total hip arthroplasty. This led to the adoption of modern highly cross-linked polyethylene in total knee arthroplasty (TKA). However, the differences in modes of wear and failure between total hip arthroplasty and TKA have tempered expectations regarding similar decreases in polyethylene-related complications in TKA. We present a case of early catastrophic failure of a modern sequentially irradiated and annealed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…A knee simulator study comparing six poly designs demonstrated the lowest wear rates with X3 poly [ 16 ]. However, early failures with fractures and oxidation damage have been reported with this design affecting mainly the posteromedial and lateral borders [ 17 ]. Although there are no long term data using X3 in TKA, the short term studies have demonstrated superior wear characteristics [ 18 , 19 ].…”
Section: Reviewmentioning
confidence: 99%
“…A knee simulator study comparing six poly designs demonstrated the lowest wear rates with X3 poly [ 16 ]. However, early failures with fractures and oxidation damage have been reported with this design affecting mainly the posteromedial and lateral borders [ 17 ]. Although there are no long term data using X3 in TKA, the short term studies have demonstrated superior wear characteristics [ 18 , 19 ].…”
Section: Reviewmentioning
confidence: 99%
“…There are only a very limited number of case reports of previous failure of the X3® in TKA, and the failure modes were different than this report. Sonn and Meneghini [ 14 ] discussed an early failure of X3® at 5 years. The mechanism of failure was a completely worn through polyethylene.…”
Section: Discussionmentioning
confidence: 99%
“…At our retrieval centre, we receive explanted TKAs from hospitals as part of routine clinical practice. For the current study, we identified all explanted fixed-bearing TKAs of four widely used contemporary designs: Attune used with an AOX antioxidant PE insert (DePuy, USA); NexGen (Zimmer, USA); PFC (Press Fit Condylar) used with D∑GVF PE (DePuy); and Triathlon used with an X3 PE insert (Stryker Orthopaedics, USA 11 ), which were revised for any indication (Figure 1).…”
Section: Methodsmentioning
confidence: 99%